Biotechnology and patent protection : an international review - Beier, Friedrich-Karl; Crespi, R. S.; Straus, Joseph (Paris : OECD, 1985)
There is no other field OF tecnnology where national patent iaws vary on so many points as they do in biotechnology. This report analyses these national divergencies and suggests changes which could lead to better legal protection of the inventor in biotechnology and to better international harmonisation of patent law.
Incluye referencia bibliográfica: p. 110-133.
Keywords: MICROORGANISMOS; PATENTES DE INVENCION